Façade material selection criteria for optimising building maintainability - Kanniyapan, Gunavathy (Penerbit UTM Press, 2015)
Maintainability of building facilities partially relies on the materials selection as their potential to resist defects from common deterioration, ease maintenance, and minimise maintenance cost can be improved throughout their designed life. Therefore, it is highly critical that during the design stage, scores of material options are identified and analysed for their suitability to achieve maintainability during post construction occupancy. This article identify a set of criteria to evaluate facade materials as to their potential contribution to post construction maintainability in built environment. Ten maintainable façade material selection criteria which is durability, cleanability, material sustainability, compatibility and suitability, health and safety, material economy, material availability, functional performance, thermal performance and acoustical had been identified by using NVIVO and content analysis on 40 selected articles. This initial findings will provide a review on the maintainability attributes that needed during selecting façade material to ensure successful implementation of design maintainability